AN ASSESSMENT OF THE CHARACTERISTICS AND DISTRIBUTION OF MICROCLIMATIC ELEMENTS IN ENUGU URBAN (Journal of Geography, Meteorology and Environment, 2021)
This paper examined the characteristics and distribution of microclimatic parameters in Enugu Urban. The data were obtained from Nigerian Meteorological Agency (NiMet). Descriptive and inferential analytical techniques were employed for data analysis. Correlation analysis was employed to determine the degree of linear association among the microclimatic elements. The result shows that annual rainfall is clustered around 1200mm and 1900mm. The skewness and kurtosis of annual rainfall estimate show positive kurtosis of 0.17. The distribution result of maximum temperature is clustered around 29.1 o C and 33.9 o C with a mean of 32.0 o C and a standard deviation of 0.7 o C. The close spread indicates that the series are not volatile. From the skewness and kurtosis statistics, it is shown that the series is negatively skewed and has an excess kurtosis of about 4.98. The result also shows that the minimum rainfall was760.09mm, recorded in the year 1983 while the maximum was 2070.10mm in the year 2012. The minimum temperature of the area ranges between 21.6 o C to 24.5 o C with a mean value of 22.4 o C and a standard deviation of 0.5 o C. The minimum value of wind speed is 2.70 knots while the maximum value is 6.90knots. The series is skewed to the left and without excess kurtosis. The relative humidity in the area stood at an average of 57.32% with a standard deviation of 2.39%, indicating the non-volatile nature of the data series. The minimum value for the period was 51.0% seen in 2015 while the maximum was 63.0% observed in 2008. The characteristics result of sunshine for the study period shows that the sunshine values (in hours) per day ranges from 5.1 to 5.8 having a mean value of 5.4 and associated standard deviation of 0.2. The series are normal, positively skewed and without excess kurtosis. The correlation analysis result shows that there is no multicollinearity problem among the variables. Rainfall interacts negatively and insignificantly with temperature, sunshine and wind speed, and positively with relative humidity. There is also a significant negative link between relative humidity and sunshine. The study therefore, reveals some evidence of urban heat island and recommends urban forestry and tree planting. It also suggests increasing the albedo of surfaces as a good mitigating measure.
Keywords: Microclimatic Elements; Distribution; Characteristics; Urban Heat Island; Urban Climate